PERANCANGAN DAN REALISASI PROTOTIP SISTEM PENGUKURAN USIA KEHAMILAN BERBASIS PC - Handayani, Budi
Abstract : This thesis describes the development of a PC-based gestational age measurement system. By measuring gestational ages, it is expected that health status can be monitored. This measurement is based on fundus of uterus length method. Both hardware and software development have been conducted. The hardware consists of a transmitter module, a receiver module, and a track counter module. The transmitter module is used to activate ultrasonic transducer so it can produce ultrasonic wave. The receiver module is used to process the reflecting waves. The track counter module is used to count a length of track that is passed over by a wheel. The software was developed based on Delphi developer II to control all the necessary hardware. Paradox Database (included in Delphi Database Desktop) was used in the development of the database system of the patients. A number of hardware tests have been conducted by measuring the output signals for each module. The software tests have been conducted by operating the program, and stored a few data on a database. The result of the whole system tests can show measurement result in centimetres, gestational age in weeks which based on Spiegelberg method, Mc Donald method, and Johnson-Tausak method. After fulfilling the necessary clinical requirement, it is hoped that the system could contribute to the enhancement of mother and child healthcare in Community Healthcare Centers.